Measuring the Effect of a Community-level Program on Women's Empowerment Outcomes : Evidence from India - Kandpal, Eeshani (World Bank, Washington, DC, 2013)
This paper uses primary data from rural north India to show that participation in a community-level female empowerment program significantly increases access to employment, physical mobility, and political participation. The program provides support groups, literacy camps, adult education classes, and vocational training for rural women in several states of India; the data are from Uttarakhand. The paper uses instrumental variables and truncation-corrected matching on primary data to disentangle the program's mechanisms, separately considering its effect on women who work, and those who do not work but whose reservation wage is increased by participation. The analysis also finds significant spillover effects on non-participants relative to women in untreated districts. It finds consistent estimates for average treatment and intent to treat effects